Incidence of Gallbladder Carcinoma in Thick Walled Gallbladder in Comparison with that of Normal Thickness A Study of 300 Cases - Hasan, Md Mahboob; Laila, Syeda Zeenat; Mamun, Md Monjur Hasan (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Gall bladder carcinoma (GBC) is the most common biliary tract cancer. Delayed presentation and early spread of tumor made it one of the lethal tumors with poor prognosis. Objective: The objective of this study is to find out the incidence of GBC in thick walled gall bladder (GB) in comparison with that of normal wall thickness. Methods: This prospective study was carried out in Combined Military Hospital (CMH) Dhaka, CMH Momenshahi and CMH Ghatail during the period of June 2007 to June 2014. A total 300 patients underwent cholecystectomy were studied retrospectively. Diagnosis was confirmed by histopathological examination. Results: Out of 300 patients 254 (84.88%) were female (male : female = 1:5.52), age range 28 to 79 years. Maximum number of the patients fall into fourth and fifth decades. 42 (14%) patients were found to have thick walled GB by preoperative sonography and during surgery. Histopathologically 13 (4.33%) patients were diagnosed as GBC. Maximum patient (52.33%) had chronic cholecystitis. Incidence of malignancy were higher (84.62%) in patients having thicke walled GB. Conclusion: GBC may present as focal or diffuse asymmetric wall thickening or even in GB having normal wall thickness. As early diagnosis and effective treatment can significantly reduce the morality and morbidity all specimen should be examined histopathologically. J Bangladesh Coll Phys Surg 2016; 34(4): 193-198